Improving fifth-grade students’ learning outcomes using the discovery learning model in integrated thematic learning - Rahdia, Rahma Ella; Lena, Mai Sri (Journal Of Teaching And Learning In Elementary Education, 2023)
The background of this research because the activities of providing material in schools many students are less active and cause their learning outcomes not to be maximized. This study uses research methods for planning, actions, observations, and reflections, and also by applying the discovery learning model. This study used 28 fifth grade students at SDN 12 Tanah Sirah Padang City as subjects. Data collection techniques through observation, non-test and test. This study produces data that shows an increase of learning activities and learning outcomes of fifth-grade students. From the results obtained, it can be concluded that the application of the discovery learning model increases the level of integrated thematic learning outcomes from students.